2007
DOI: 10.1016/j.smrv.2007.01.002
|View full text |Cite
|
Sign up to set email alerts
|

The metabolic consequences of sleep deprivation

Abstract: The prevalence of diabetes and obesity is increasing at an alarming rate worldwide, and the causes of this pandemic are not fully understood. Chronic sleep curtailment is a behavior that has developed over the past 2-3 decades. Laboratory and epidemiological studies suggest that sleep loss may play a role in the increased prevalence of diabetes and/or obesity. Current data suggest the relationship between sleep restriction, weight gain and diabetes risk may involve at least three pathways: 1. alterations in gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

23
767
4
47

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 1,112 publications
(877 citation statements)
references
References 102 publications
23
767
4
47
Order By: Relevance
“…The finding that genetic variation within the MTNR1B gene region affects glucose levels and risk of type 2 diabetes is not surprising, given that melatonin has an inhibitory effect on insulin release and that MTNR1B is transcribed in human pancreatic islets [3,9]. Furthermore, sleep disturbances and altered circadian rhythm have previously been linked to metabolic dysfunction, including type 2 diabetes [7,8]. These recent studies have provided additional knowledge regarding the mechanisms by which the melatonin system contributes to this pathogenic process [2,3].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The finding that genetic variation within the MTNR1B gene region affects glucose levels and risk of type 2 diabetes is not surprising, given that melatonin has an inhibitory effect on insulin release and that MTNR1B is transcribed in human pancreatic islets [3,9]. Furthermore, sleep disturbances and altered circadian rhythm have previously been linked to metabolic dysfunction, including type 2 diabetes [7,8]. These recent studies have provided additional knowledge regarding the mechanisms by which the melatonin system contributes to this pathogenic process [2,3].…”
Section: Discussionmentioning
confidence: 99%
“…As a highly lipophilic circulating hormone, melatonin easily reaches and penetrates all cells and, in addition to controlling circadian rhythm, it has the ability to neutralise reactive oxygen and nitrogen species and activate the immune system [6]. Several studies have shown a link between disturbances of circadian rhythm and metabolic diseases, including diabetes [7,8], as well as a clear relationship between insulin and melatonin [9]. Two distinct G proteincoupled receptors, MTNR1A and MTNR1B, mediate the effects of melatonin.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanisms underlying the association between short or long sleep duration and cancer risk are not fully understood. Two potential biological mechanisms have been proposed to explain how short sleep duration directly influenced cancer incidence, including impaired immune function and metabolic pathways related to obesity (Knutson et al, 2007;Marshall et al, 2008). Moreover, the altered melatonin secretion has also been shown as a potential risk factor of cancer (Stevens et al, 2007;Benke et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Estudos experimentais têm demonstrado que a privação parcial do sono pode levar a alterações hormonais, as quais podem retornar a um nível mais normal e funcional após um período de recuperação de sono 21 . Outra forma de compensação das horas de sono perdidas pode ser a sesta.…”
Section: Discussionunclassified